Pieczęcie monarsze epoki piastowskiej i jagiellońskiej w zbiorach archiwum klasztoru Bożego Ciała w Krakowie. Przyczynek do polskich badań sfragistycznych - Łatak Kazimierz (Saeculum Christianum, 2022)
This article presents the seals of the Polish monarchs of the Piast and Jagiellonian dynasties held in the archives of the Corpus Christi monastery of the Canons Regular in Krakow. These seals constitute a small part of the collection, which comprises no less than a thousand wax and paper specimen, but they are nevertheless valuable for many reasons, as they possess a great deal of information potential. They have been mentioned in the scientific literature and reproductions of several of them have been used as illustrative material for prestigious publications but have not yet been the subject of separate research interest or description. The oldest of the seals presented in the article dates from 1327 and is an imprint of the seal of King Władysław Łokietek (†1333), while the last one dates from 1549 and is an imprint of the seal of King Zygmunt August (†1572). The article is only an extended introduction to a more thorough and multifaceted study and has a contributory character. A review of the Polish sphragistic literature signals that publications on seal collections in church archives are scarce. Therefore, the proposed article will fill this gap, at least to a small extent, and above all, introduce information about this collection into the scientific circulation.